Sliding interaction and wear studies between two hemispherical asperities based on finite element approach. (27th June 2008) - Shankar, S.; Mayuram, M.M.
A better insight of the wear as well as frictional process is possible by understanding the nature of the sliding interactions between the two contacting asperities. A Finite Element Method (FEM) is developed to calculate the wear depth and volume of material displaced laterally between two contacting asperities during sliding. Two three-dimensional hemispherical asperities with varying overlaps are modelled, the normal force acting on the asperity, shear force and the overall friction coefficient are determined for different E/Y ratios. Wear prediction can then be attempted by combining the influences of contact stress and a surface wear coefficient.